Ecotourism and Its Relation to the Wildlife Opportunities: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The rising demand for tourism goods adds to increased pressure on our natural capital and other resources. In recent years, ecotourism in the developed world in particular gained a lot of coverage. Eco-tourism can also be termed as management of tourism and conservation of nature in a way so as to maintain a fine balance between the requirements of tourism and ecology on the one hand and needs of the local communities for jobs, new skills, income generating employment and a better status for women on the other. It also aims at educating visitors, advising tourists, delivering ecological restoration funds that offer direct benefits to local communities and regions in their economic growth and political empowerment, and encouraging respect for diverse cultures and human rights. New ecotourism enhancements in Uttar Pradesh have been started, where tourists can access enhanced tourism resources such as hosting, field facilities, etc. This has led to ecotourism being encouraged in the state. In India the number of tourists arriving both domestic and international has risen considerably since 2000. The largest share of these tourists has been received by Uttar Pradesh in 2019, Uttar Pradesh was 2nd among all States with respect to domestic tours and 3rd in terms of tourism abroad in India. This optimistic tourism figures in Uttar Pradesh will directly and indirectly build jobs for both professional and non-trained employees. It is also a big problem for the future, such as the shortage of decent tourism services, global health and tourism safety issues, etc. The goal of this document is to discuss the possibilities and challenges of ecotourism in Uttar Pradesh with a specific emphasis on job development.